PEMBACAAN SURAH AL-FATIHAH SEBAGAI MEDIA PENGOBATAN : (Sebuah Kajian Living Qur’an pada Fenomena Masyarakat Kelurahan Kembang Paseban Kabupaten Batang Hari Provinsi Jambi) - Reno Yulianda (EL-ADABI : Jurnal Studi Islam, 2024)
This study explores the phenomenon of Surah Al-Fatihah which is used as a treatment using fresh water media. In this study, the main object is aimed at the people of Kembang Paseban Village on the grounds that they strongly believe that using the method of treatment through the media of fresh water that is recited Qur'anic verses as well as prayers can provide blessings and benefits, especially healing for various diseases. The result of this research is to find out what kind of process is done in the treatment, what are the verses that are read and how is the understanding of the community related to treatment using fresh water media. This research was conducted with a qualitative research method (field research) which is descriptive-analytical in nature. It is explained that descriptive-analysis seeks to describe and explain the data that has been obtained from the results of the author's interviews with the people of Kembang Paseban regarding the phenomenon of Surah Al-Fatihah as a treatment using freshwater media. This researcher has several tools in collecting data, namely observation, interviews, and documentation. The results of the research that has been done by the author can be known that the people of Kembang Paseban Village believe that treatment with fresh water media read Surah Al-Fatihah, Shalawat repeated up to three times as well as prayer can provide healing for various diseases. The people of Kembang Paseban Village with their awareness of treatment with fresh water media so much contains the blessings obtained. It can be clarified that to bring healing must be with the permission of God the Almighty creator. The affirmation of the word syifa' in the Qur'an is a source of syifa' (healer), it is necessary to know that the human soul is called the nafs element, which is something that can be restored by reading the verses of the holy book.